Estimating the critical parameters of the hard square lattice gas model. (3rd April 2017) - Mandal, Dipanjan; Nath, Trisha; Rajesh, R
Abstract: The hard square lattice gas model on a square lattice is known to undergo a continuous phase transition from a low density fluid-like phase to high density phase with columnar or smectic order. We estimate the critical activity z c by calculating, within an approximation scheme, the interfacial tension between two differently ordered columnar phases, and then setting it to zero. The approximation scheme allows for the ordered phases to have multiple defects and the interface between the ordered phases to have overhangs. We estimate z c = 105.35, which is in good agreement with existing Monte Carlo simulation results of z c ≈ 97.5, and is an improvement over earlier best estimates of z c = 54.87 and z c = 135.63.